Student satisfaction level among allied health sciences students at King Edward Medical University - Afisa Bashir; Shahzaib Ahmad; Muhammad Zeeshan Sarwar; Syed Asghar Naqi (Intelektual Pustaka Media Utama, 2021)
The purpose of this study was to evaluate student satisfaction with their program, academic environment and administrative services in terms of its effectiveness on their professional attitudes, lives and career. A total of 261 students of allied health sciences program at King Edward Medical University, were examined in terms of personal satisfaction by means of a specifically designed student satisfaction survey. A qualitative analysis approach was used to interpret the data generated by a three‐part survey form circulated to the four proceeding sessions of allied health sciences program and satisfaction of students in 12 major disciplines was evaluated. The data was entered in statistical product and service solutions (SPSS) version 22 using quantitative variables and descriptive statistics including frequency distribution tables and diagrams. The study revealed a student satisfaction of only 22.1% with their program with different levels of recommendation in different sub-disciplines. A total of 20.9% students agreed to the library facilities, 53.9% with computer lab, 35% with administrative support, 29.6% with sports facilities and 49% with teaching methodologies. The present study concludes that most of the students had little satisfaction concerning their field of study. So, it is necessary to make an attempt for continuous development of quality services.